Analysis of Teacher's Authority to Discipline VB Class Participants at SDN 3 Monument Tasikmalaya - Kinjani Merawati, Listya; Nugraha, Fajar; Zahara Nurani, Riga (Yayasan Mentari Madani, 2024)
Discipline during the learning process is crucial to achieve the desired learning objectives. However, the reality is that there are still students who lack discipline during the learning process. Therefore, the teacher's authority is essential to achieve a high level of learning discipline. This research focuses on the characteristics of teacher authority: (1) neat appearance, (2) ability to reprimand students, (3) performance in facing problems, (4) enforcer of discipline, (5) as a role model, and discipline during the learning process, namely: (1) speaking when the teacher is explaining, (2) inability to stay seated when the teacher is checking students' work, (3) not completing tasks/exercises within the specified time. This research aims to determine the efforts of teacher authority to discipline students. The research method used is qualitative descriptive research. In this study, data collection techniques used by researchers include observation, interviews, and documentation. Based on the observations and interviews conducted by the researcher on the students, the results obtained include: (1) talking outside the learning discussion, (2) disturbing other students, (3) not completing tasks. Regarding teacher authority, the teacher already possesses the mentioned characteristics and makes efforts mentioned to discipline students during the learning process.